(untitled) (Alternautas, 2014)
What is Buen vivir, why is it interesting, and what makes it relevant beyond its birth-land in the Andean-Amazonian region of the Americas? Is it aything new at all, or is it just a rehashed and overrated discourse? What prospects are there for Buen vivir as the organizing principle of a cultural model for global sustainability? In the limited space of the article that follows, we intend to explore these and similar questions around an idea that has unexpectedly popped-up in global academic and political debates in recent years.